Role of an extracellular loop in determining the stoichiometry of Na(+)–HCO(3)(−) cotransporters - Chen, Li-Ming (Blackwell Science Inc, 2011)
The Na(+)–HCO(3)(−) cotransporters (NBCs) of the solute carrier 4 family (SLC4) are critical for regulating pH in cells as well as in fluids such as blood and cerebrospinal fluid. Moreover, mutations and gene disruptions in NBC are linked to a wide range of pathologies. NBCe1 (SLC4A4) is electrogenic because it has an apparent Na(+):HCO(3)(−) stoichiometry of 1:2 or 1:3, whereas NBCn1 (SLC4A7) is electroneutral because it has an apparent stoichiometry of 1:1. Because stoichiometry influences the effect of transport on membrane potential and vice versa, a central question is what structural features underlie electrogenicity versus electroneutrality. A previous study on rat NBCe1/n1 chimeras demonstrated that the structural elements determining the electrogenicity of NBCe1-A are located within the transmembrane domain, excluding the large third extracellular loop. In the present study we generated a series of chimeras of human NBCe1-A and human NBCn1-A. We found that replacing merely the predicted fourth extracellular loop (EL4) – containing 32 amino acid residues that include 7 prolines – of human NBCe1-A with EL4 of NBCn1-A creates an electroneutral NBC. The opposite switch converts an electroneutral construct to one with electrogenic properties. The introduction of an N-glycosylation site into EL4 confirms that at least a part of it is exposed to the extracellular fluid. We hypothesize that putative EL4 either contributes to the substrate-binding vestibule or indirectly influences substrate binding by interacting with one or more transmembrane segments, thereby controlling the nature of transport.